2004
DOI: 10.1007/s10384-003-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Analysis for Detecting Early Glaucomatous Changes in Ocular Hypertension Using Optical Coherence Tomography

Abstract: Early glaucomatous RNFL changes might exist in some areas of ocular-hypertensive eyes, and a symmetry analysis may be a useful method for detecting these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…These conclusions are confirmed in other studies which establish the role of OH as a risk factor for the development of POAG 23. However, earlier studies came to different conclusions and did not report any differences in thicknesses between normal and ocular hypertensive eyes 24.…”
Section: Discussionsupporting
confidence: 76%
“…These conclusions are confirmed in other studies which establish the role of OH as a risk factor for the development of POAG 23. However, earlier studies came to different conclusions and did not report any differences in thicknesses between normal and ocular hypertensive eyes 24.…”
Section: Discussionsupporting
confidence: 76%
“…More recently, Hoh et al 11 and Sugimoto et al 33 observed that OCT could not differentiate between normal and OHT eyes, even though the authors admitted that early changes may exist in some patients with OHT. 33 In the present study, we found significant differences between normal eyes and OHT eyes in optic disc parameters, as Zangwill et al 31 previously observed, but not in RNFL thickness. The significant differences in disc parameters could mean that some study participants in the OHT group had early glaucomatous changes not detected by standard field testing.…”
Section: Discussionsupporting
confidence: 76%
“…The retinal nerve fiber layer, retinal capillary perfusion, astigmatic axis, higher-order aberrations (HOAs), and overall corneal thickness, as well as the epithelial thickness, have similar patterns, mirror-symmetric patterns, or both. [1][2][3][4][5][6][7][8][9][10][11] Minimum corneal thickness (MCT) is an important parameter in surgical planning and in the detection of pathology in certain corneal and refractive surgery procedures, in which accurate assessment of MCT and its location is crucial. [12][13][14][15][16] Errors in pachymetric measurement are factors in poor surgical outcomes, including ectasia after laser in situ keratomileusis.…”
Section: Discussionmentioning
confidence: 99%